Magneto-thermoelastic interactions in generalized thermoelastic half-space for varying thermal and electrical conductivity - Tiwari R. (My University, 2025)
Significant variations are observed over the working temperature range of the various engineering problems such as designing the structures heated by sudden heat flux in engineering. At that time, major variations in the coefficient of the thermal conductivity of the material are observed. Electrical conductivity is also found to be directly dependent on the thermal conductivity. Therefore, present problem enlightens the influence of the variable thermal conductivity and electrical conductivity inside a half space medium permeated by the magnetic field in context of dual phase lag thermoelasticity. Thermal shock has been applied to the non-traction boundary of the medium. Analytical solutions are calculated by adopting Laplace transform technique. Physical fields such as conductive temperature, displacement as well stress of the medium are evaluated in time-domain numerically by using a suitable method of numerical inversion of Laplace transform. Further, to predict the utility of the present model, computational results are compared to the corresponding results of heat conduction model with single phase lag (Lord and Shulman model). By examining the numerical results that have been graphically represented, significant differences have been attributable to the studied fields due to the variable thermal conductivity and different heat conduction models. © 2021 Informa UK Limited, trading as Taylor & Francis Group.